2017
DOI: 10.1093/ecco-jcc/jjx027
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Rectal Neoplasia after Colectomy and Ileorectal Anastomosis for Ulcerative Colitis

Abstract: The risk of rectal carcinoma in patients with IRA for UC remains, and this justifies long-term endoscopic surveillance. Either IPAA or end ileostomy should be considered in 'high-risk' patients i.e. those with PSC and/or with prior colonic neoplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 16 publications
5
31
0
3
Order By: Relevance
“…Pouch dysfunction can occur following surgery and can be caused by pouchitis, cuffitis, irritable pouch syndrome, CD, or pouch fistula. Pouch failure requiring surgery and removal of pouch can sometimes occur [372] and diagnosis depends on endoscopic and histological findings in conjunction with symptoms [376]. Some patients with symptoms of pouchitis will not have inflammation, but rather, irritable pouch syndrome [372].…”
Section: Caring For the Patient With An Ileoanal Pouch N-ecco Statemementioning
confidence: 99%
“…Pouch dysfunction can occur following surgery and can be caused by pouchitis, cuffitis, irritable pouch syndrome, CD, or pouch fistula. Pouch failure requiring surgery and removal of pouch can sometimes occur [372] and diagnosis depends on endoscopic and histological findings in conjunction with symptoms [376]. Some patients with symptoms of pouchitis will not have inflammation, but rather, irritable pouch syndrome [372].…”
Section: Caring For the Patient With An Ileoanal Pouch N-ecco Statemementioning
confidence: 99%
“…The function following conversion of an IRA to a pouch seems reasonable in patients with familial adenomatous polyposis, and probably in patients with UC . Another disadvantage with IRA is the potential risk of cancer, and yearly surveillance of the rectal remnant is needed .…”
Section: Discussionmentioning
confidence: 99%
“…The function following conversion of an IRA to a pouch seems reasonable in patients with familial adenomatous polyposis, and probably in patients with UC [19,20]. Another disadvantage with IRA is the potential risk of cancer, and yearly surveillance of the rectal remnant is needed [21,22]. IRAs have the perceived advantage of being less technically demanding and, in combination with careful patient selection and medical management of the rectal remnant, may represent an interim measure for some patients requiring colectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown safety of IRA for UC with overall complications ranging from 24% to 28% and anastomotic leak rate of 3-4% [67][68][69]. Long-term failure rate is the most important concern and ranges from 18% to 49% [67,[69][70][71]. In a recent multicenter retrospective study of 343 patients undergoing IRA in France, multivariable analysis identified treatment with both immunosuppressants and anti-TNF before colectomy as independent predictors of IRA failure, whereas colectomy for severe acute colitis was associated with a decreased risk of IRA failure [72].…”
Section: Ileorectal Anastomosismentioning
confidence: 99%